Double Standards in International Legal Politics in the Settlement of Violations of Human Rights to the Rohingya Ethnic - Maziyyah, Rifdatul; Shohihah, Millatus; Syndo, Sivana Amanda Diamita; Murtadho, Nazhif Ali (International Journal of Law Dynamics Review, 2023)
This article aims to identify the resolution of gross human rights violations against the Rohingya ethnic group who have been discriminated of the Myanmar Military Junta Government. The international community and political response are giving pressure and criticism about upheaval against the settlement of violations against the Rohingya. The Myanmar government rejection of accusations of gross human rights violations can be seen from the international double standards towards the settlement of the Rohingya case. This article uses the library research method, and critical analysis to understand the settlement of human rights violations against the Rohingya. The conclusion is Discrimination against this ethnic can be considered by international human rights law as a gross violation of human rights, even though Myanmar has legal arrangements for protecting human rights in force in its country. International human rights law as a political instrument has powerful in efforts to create quality international policy products including guaranteeing the implementation of respect for human rights in the world through the role of international institutions as guardians in the process of enforcing human rights violations committed by a country through various strategic steps both repressive, preventive and curative. Discrimination against the Rohingya can be seen in the application of double standards by several countries such as the Western block countries, where they seem to keep quiet about these human rights violations.